Chrysobrycon yoliae, a new species of stevardiin (Characiformes: Characidae) from the Ucayali basin, Peru - Vanegas Rios, James Anyelo (2014)
Chrysobrycon yoliae, new species, is described from a drainage flowing into the río Yucamia basin, río Ucayali basin, Peru. Chrysobrycon yoliaeis readily distinguished from its congeners by the anterior tip of pelvic bone situated anterior to the fifth rib (vs. situated posterior to the fifth rib), the presence of 20-26 dentary teeth (vs. 11-19), and the possession of a terminal lateral-line tube between caudal-fin rays 10 and 11 (vs. the absence of this tube, except in C. eliasi). The new species differs from C. eliasi and C. myersi by the presence of teeth on third pharyngobranchial (vs. the absence of teeth on this bone) and also differs from C. eliasi by the dorsal-fin origin situated at vertical through anal-fin rays 5 to 7 (vs. located at vertical through anal-fin rays 8 to 10), the posterior extent of the ventral process of quadrate reaching the vertical through posterior margin of symplectic (vs. not reaching the vertical through posterior margin of symplectic), the dorsal-fin to adipose-fin length 26.8-28.8% SL (vs. 23.9-26.8% SL), and the body depth at dorsal-fin origin 34.4-42.2% SL (vs. 24.1-34.5% SL). A key for the identification of Chrysobrycon species is provided.